Iron and Steel Division - Effects of Manganese and Its Oxide on Desulphurization by Blast-Furnace Type Slags - Discussion - Nicholas J. Grant; Ulf Kalling; John Chipman (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1952)
D. E. Babcock (Republic Steel Corp., Youngstown, Ohio)—I would like to know what evidence you have to prove the MnO was pure MnO. I would also like to know whether you might not explain it on the basis of a temperature reversion; and, was it due to the oxidizing power of MnO? N. J. Grant (authors' reply)—Briefly, we have no proof that pure MnO was used. The manganese oxide was added as chemically pure MnO,. MnO is assumed as the oxide in the reacted slag following standard molecular slag theories, especially under the reducing conditions of these experiments. The noted sulphur reversion cannot by any means be explained on the basis of a temperature reversion since the temperature effect is shown in this paper to be very small. Until a more logical explanation can be offered, backed I hope by some experimental proof, we propose to explain this sulphur reversion as stated in the paper, namely, that it is due to the oxidizing effect of the added manganese oxide. Member—How did the oxygen in the slag give you a reversion of sulphur? What was the mechanism there?